USING GAP INFORMATION ACTIVITY IN TEACHING ENGLISH AT HOTEL AND TOURISM VOCATIONAL HIGH SCHOOL - Suci Ayu Andari; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2016)
In this paper the writer discusses some of the activities of information sharing (gap information) in learning English at hotel and tourism vocational high school. This paper describes the activity of sharing information in study speaking in the class. This activity is best used as a technique to learn speaking so that, when students learn speaking they feel comfortable, easy to understand and not boring. So that this information sharing activity (gap information) can help students to improve their speaking skills